Persepsi dan Implementasi Program Studi Pengembangan Masyarakat Islam di Indonesia - Abd. Gappar Yusuf; Fitri Yanti; Bambang Budiwiranto; Faizal Faizal; Tontowi Jauhari (Ridwan Institute, 2024)
The development of community development science has been studied by Western countries since 1925, with a focus on social development and community welfare. In 1995, Indonesia underwent a knowledge transformation by introducing the applied science of Islamic Community Development, which combines social science and Islamic values. The Islamic Community Development program has been popular in Indonesia until 2023 but remains unknown internationally. The aim of this research is to analyze the perception of the program and the implementation of Islamic community development theories on society as the focal point of community development studies in Indonesia. This research is a qualitative analysis with a phenomenological approach and a holistic perspective. Data collection was conducted through focus group discussions, observations, interviews, and document studies. The results of this research analyze that: (1) The perception of the Islamic community development program, in terms of concepts, scope, and goals, still varies among individuals, thus requiring a comprehensive concept to align perceptions regarding the Islamic community development program.